2022
DOI: 10.3233/cbm-200986
|View full text |Cite
|
Sign up to set email alerts
|

Delta-like ligand 4 level in colorectal cancer is associated with tumor aggressiveness and clinical outcome

Abstract: BACKGROUND: The Notch signaling regulates numerous cell growth, differentiation, and death. However, the expression pattern of its ligand Delta-like 4 (DLL4) in tumors is still uncertain. OBJECTIVE: In the present study, we examined DLL4 expression in colorectal cancer as well as assessed its role as a prognostic indicator in the present study. Methods: DLL4 expression was examined by immunohistochemistry in 265 surgically resected specimens of colorectal cancer and adjacent normal tissues. The relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…For example, delta-like 4 protein (DLL4) increases vessel branching and promotes cancer-associated modifications of the TME [ 105 ]. DLL4 was associated with tumour aggressiveness and an unfavourable clinical outcome in colorectal cancer patients [ 106 ]. Integrins are a family of proteins that direct exosomes to specific tissues, thus being partly responsible for premetastatic niche formation and metastatic tropism during breast cancer development [ 107 ].…”
Section: Exosomal Proteins In Cancer Progressionmentioning
confidence: 99%
“…For example, delta-like 4 protein (DLL4) increases vessel branching and promotes cancer-associated modifications of the TME [ 105 ]. DLL4 was associated with tumour aggressiveness and an unfavourable clinical outcome in colorectal cancer patients [ 106 ]. Integrins are a family of proteins that direct exosomes to specific tissues, thus being partly responsible for premetastatic niche formation and metastatic tropism during breast cancer development [ 107 ].…”
Section: Exosomal Proteins In Cancer Progressionmentioning
confidence: 99%
“…Multiple studies have indicated that high levels of DLL4 expression 10 , particularly within tumor tissue, are positively correlated with tumor invasiveness and poor prognosis in patients with colorectal cancer, gastric cancer, and breast cancer. 11 , 12 , 13 The study found a major correlation between increased DLL4 expression in ovarian cancer patients 14 and increased Notch intracellular cleaved domain (NICD) in colorectal cancer patients with a poor response to anti‐VEGF therapy. 3 Moreover, studies have shown that inhibiting the Notch/DLL4/Hes pathway can lead to a decrease in angiogenesis and tumor growth in human colon tumors.…”
Section: Introductionmentioning
confidence: 96%
“…Numerous clinical tumor models have demonstrated a strong correlation between DLL4 expression and tumor progression, as well as treatment resistance. Multiple studies have indicated that high levels of DLL4 expression 10 , particularly within tumor tissue, are positively correlated with tumor invasiveness and poor prognosis in patients with colorectal cancer, gastric cancer, and breast cancer 11‐13 . The study found a major correlation between increased DLL4 expression in ovarian cancer patients 14 and increased Notch intracellular cleaved domain (NICD) in colorectal cancer patients with a poor response to anti‐VEGF therapy 3 .…”
Section: Introductionmentioning
confidence: 97%